Conserving biodiversity takes a plan: How planners implement ecological information for biodiversity conservation - Gagné, Sara A. (Ambio, 2019)
Conserving biodiversity is critical to the sustainability of human settlements, and stands to benefit from collaboration between ecologists focused on understanding natural systems and planners balancing social, environmental, and economic priorities. Drawing from the socially-situated definition of ‘sustainability’, we sought to understand the relationship between ecologists and planners by probing how planners in the southeastern US prioritize and engage with biodiversity conservation and ecological information, and how context influences these decisions. We find that context matters, e.g., higher jurisdictional population density was positively associated with prioritizing tree cover and diversity. We find, also, that while biodiversity conservation and ecological information are valuable to planners, planners rely heavily on their colleagues to inform conservation-related activities and prioritize conservation topics that differ from ecological research foci. Improved communication by ecologists and context-specific transdisciplinary sustainability research, especially that which incorporates the primary role of elected officials in biodiversity conservation, may help to integrate ecological science and planning practice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13280-019-01281-z) contains supplementary material, which is available to authorized users.